(untitled) (International Journal of Ecophysiology, 2023)
In recent years, stem cell therapy has become a very promising and advanced scientific research topic. The development of treatment methods has evoked great expectations, not only researchers but also society due to its potency in cell-based therapy. Stem cells are unspecialized cells of the human body. They are able to differentiate into any cell of an organism and have the ability of self-renewal. Broadly speaking, the application of stem cells can be divided into two, namely: autotransplantation (donor and recipient are same person) and allotransplantation (donors and recipients are people who different). However, other applications namely xenotransplantation (donor and the recipient is the species that different) now it also becomes center of attention. Since it is challenging to isolate stem cells, molecular methods specifically the use of a DNA microarray, are one way to find stem cells. Microarrays have been applied in stem cell research to identify major features or expression signatures that define stem cells and characterize their differentiation programs toward specific lineages. This paper is a review focused on a discussion of the of the microarray technology and types of stem cell transplant.